The Role of Guidance and Counseling in Forming Pancasila Student Profiles - Ramadhan, Muhammad Qadri; Shobabiya, Mahasri (Sosiosaintika, 2024)
The negative impact of digitalization on students' personal development and moral degradation highlights the urgency of character education as a solution. The government's strategic plan for implementing the Pancasila student profile requires the contribution of counselors as front guards in strengthening character education in schools. This study aims to describe the role of Islamic guidance and counseling on shaping the profile of Pancasila students. The research method applied in this paper is qualitative research with a literature study approach. The researchers gathered the data from supporting articles, books, and research publications. This research reveals that the innovative programs such as online consultations, intensive character courses, and the role of Pancasila student agents are also explained as concrete efforts in achieving character education goals. A proper understanding of the role of counselors in harmonizing the Pancasila student profile, as well as the urgency of awareness and commitment of all school members to achieve intelligent students with character in national and state life.